2010
DOI: 10.1016/j.renene.2009.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel and numerical study of a small vertical axis wind turbine

Abstract: Abstract:This paper presents a combined experimental and computational study into the aerodynamics and performance of a small scale Vertical Axis Wind Turbine (VAWT). Wind tunnel tests were carried out to ascertain overall performance of the turbine and two and three dimensional unsteady computational fluid dynamics (CFD) models were generated to help understand the aerodynamics of this performance.Wind tunnel performance results are presented for cases of different wind velocity, tip-speed ratio and solidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
312
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(336 citation statements)
references
References 3 publications
16
312
0
8
Order By: Relevance
“…In terms of the manufacturing process and fabrication costs, the Darrieus rotor-straight blade or giromill showed a reliable configuration. The two blades of the giromill are generally named the H-rotor (Mertens et al, 2003, Howell et al, 2010. Hence, a deep consideration and review will be conducted on the Darrieus rotor-straight blade.…”
Section: Vertical Axis Wind Turbine (Vawt)mentioning
confidence: 99%
“…In terms of the manufacturing process and fabrication costs, the Darrieus rotor-straight blade or giromill showed a reliable configuration. The two blades of the giromill are generally named the H-rotor (Mertens et al, 2003, Howell et al, 2010. Hence, a deep consideration and review will be conducted on the Darrieus rotor-straight blade.…”
Section: Vertical Axis Wind Turbine (Vawt)mentioning
confidence: 99%
“…The external dimensions are 14D x 30D x 12D and the wall distance is 1*10-4c, necessary for an averaged y+ < 5, following a mesh sensitivity analysis performed in order to verify if the grids adopted were sufficiently fine to resolve the primary flow features. Figure 1 shows the analysis for the 2D model for the 17m Darrieus VAWT and the 3D model for the small H-Darrieus VAWT; the 3D model of the SANDIA turbine has been excluded from this analysis due to the high number of cells of the domain, but the mesh adopted is similar to that used by Howell [16] and Zhang [17].…”
Section: Numerical Approachmentioning
confidence: 99%
“…One advantage of the 3D approach could be a better estimation of dynamic stall and also lag effects due to the unsteady flow. The 2D CFD models cannot fully describe the complex dynamics of the flow whilst the 3D CFD model can take into account the near and far field flow developments surrounding the real geometry of the wind turbine, as also shown by Howell [16]. Figure 3 compares the predicted and measured coefficient of power (c p ) and power production curves for the SANDIA 17m Darrieus turbine.…”
Section: Verification Of the Cfd Modelmentioning
confidence: 99%
“…The straight turbine rotor blade, with an aspect ratio of 4:1, operates at relatively low tip speeds and its performance shows a clear dependence on the rotor blade surface finish. Performance is enhanced by having the surface of the turbine roughened at a critical Reynolds number 30,000 [13]. Fang Feng combined Savonius rotor with H-rotor and reported that, H-rotor is self-started at low tip speed ratio [14].…”
Section: Introductionmentioning
confidence: 99%